Empagliflozin improves endothelial and cardiomyocyte function in human heart failure with preserved ejection fraction via reduced pro-inflammatory-oxidative pathways and protein kinase Gα oxidation. Issue 2 (12th May 2020) - Kolijn, Detmar; Pabel, Steffen; Tian, Yanna; Lódi, Mária; Herwig, Melissa; Carrizzo, Albino; Zhazykbayeva, Saltanat; Kovács, Árpád; Fülöp, Gábor Á; Falcão-Pires, Inês; Reusch, Peter H; Linthout, Sophie Van; et al.
Abstract: Aims: Sodium-glucose-cotransporter-2 inhibitors showed favourable cardiovascular outcomes, but the underlying mechanisms are still elusive. This study investigated the mechanisms of empagliflozin in human and murine heart failure with preserved ejection fraction (HFpEF). Methods and results: The acute mechanisms of empagliflozin were investigated in human myocardium from patients with HFpEF and murine ZDF obese rats, which were treated in vivo . As shown with immunoblots and ELISA, empagliflozin significantly suppressed increased levels of ICAM-1, VCAM-1, TNF-α, and IL-6 in human and murine HFpEF myocardium and attenuated pathological oxidative parameters (H2 O2, 3-nitrotyrosine, GSH, lipid peroxide) in both cardiomyocyte cytosol and mitochondria in addition to improved endothelial vasorelaxation. In HFpEF, we found higher oxidative stress-dependent activation of eNOS leading to PKGIα oxidation. Interestingly, immunofluorescence imaging and electron microscopy revealed that oxidized PKG1α in HFpEF appeared as dimers/polymers localized to the outer-membrane of the cardiomyocyte. Empagliflozin reduced oxidative stress/eNOS-dependent PKGIα oxidation and polymerization resulting in a higher fraction of PKGIα monomers, which translocated back to the cytosol. Consequently, diminished NO levels, sGC activity, cGMP concentration, and PKGIα activity in HFpEF increased upon empagliflozin leading to improved phosphorylation of myofilament proteins. In skinned HFpEF cardiomyocytes, empagliflozin improved cardiomyocyte stiffness in an anti-oxidative/PKGIα-dependent manner. Monovariate linear regression analysis confirmed the correlation of oxidative stress and PKGIα polymerization with increased cardiomyocyte stiffness and diastolic dysfunction of the HFpEF patients. Conclusion: Empagliflozin reduces inflammatory and oxidative stress in HFpEF and thereby improves the NO–sGC–cGMP–cascade and PKGIα activity via reduced PKGIα oxidation and polymerization leading to less pathological cardiomyocyte stiffness.